ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRICE EARNING RATIO SAHAM PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Azmi, Fika (PRESTASI, 2013)
ABSTRAKStock valuation is a very important factor in the investment of stock. One of the best methods of this analysis is Price Earning Ratio. It based on the ratio between price per share in the stock market and available net profit for the stockholders. Price earning ratio is applied to identify the stock to buy or sell. This study tries to analyze the influence of several faktors affecting price earning ratio of stock listed on Indonesia Stock Exchange, i.e.: sales growth, growth of return on equity, dividend payout ratio, SBI interest rate, inflation rate, and growth of debt to equity ratio. Observation period is from 2009 to 2012. The populations on this study is all companies that are listed on IDX and have data of the stock closing price and earning per share. The criterion to choose sampels is the companies do not implement policies affecting price and number of stock. By using multiple linear regression, this study indicates that multicollinearity exist in the model; therefore the growth of debt to equity ratio is not included in the model. Statistik test shows that the analyzed faktor simultaneously affect the price earning ratio of stocks in IDX, and able to explain 94,1 %. Individual analysis indicates that dividend payout ratio an SBI interest rate affect significantly, but theoretically, the influential factors in analyzing price earning ratio for stock listed on ISX is only dividend payout ratio. This result is consistent with previous study by Arfentyas (1999).Keyword: Price earning ratio, closing price, earning per share, dividend payout ratio.